VIABILITAS BAKTERI ASAM LAKTAT YANG DIISOLASIDARIAMPAS SUSU KEDELAI TERHADAP ASAM KLORIDA DAN GARAM EMPEDU - Zulfidin Zulfidin; Evy Rossi; Akhyar Ali (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Lactic acid bacteria have characteristics that cause these bacteria as probiotics. Some characteristics of probiotics are not only able to survive in the gastrointestinal tract and also have the ability to reproduce in the digestive tract, but these bacteria can survive and are able to live on acidic conditions of chloride with low pH and bile salts. The purpose of this study was to obtain resistance or viability of lactic acid bacteria isolated from okara at pH 2.5 and 3 for 90 min and 0.5% concentration of bile salt (oxgall). This study used isolates A.23.4, A.23.2, and A.22.4 isolated from okara taken from soybean milk making industrial home. The isolate viability data was tabulated and analyzed descriptively. The results showed that isolates A.23.4, A.23.2 and 22.4 survived and were able to grow well at pH 2.5 and had survival 99.786, 99,773, and 99.899% respectively, while at pH 3 viability were 99.887, 99.824, and 99.836% for 1.5 hours incubation. Isolates A.23.4, 23.2, and 22.4 were able to survive and grow well in MRS Broth medium plus oxgall 0.5% during incubation for 5 hours and viability of 99.759, 99.657, and 99.619% respectively.  From this study, it can be concluded that the three isolates of LAB had potential as probiotics candidates, because they have relatively high viability (> 90%) on low pH and bile salt.Keywords:  lactic acid bacteria, probiotic, viability, chloride acid, oxgall, isolate